2009
DOI: 10.1152/japplphysiol.91654.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between muscle temperature and contraction velocity affects mechanical efficiency during moderate-intensity cycling exercise in young and older women

Abstract: The effect of elevated muscle temperature on mechanical efficiency was investigated during exercise at different pedal frequencies in young and older women. Eight young (24 +/- 3 yr) and eight older (70 +/- 4 yr) women performed 6-min periods of cycling at 75% ventilatory threshold at pedal frequencies of 45, 60, 75, and 90 rpm under control and passively elevated local muscle temperature conditions. Mechanical efficiency was calculated from the ratio of energy turnover (pulmonary O(2) uptake) and mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…A number of studies have investigated the laboratory practice of recording these measures [19,23,28,32], the impact of training status and interventions [1,7,15,16,17,26], gender [3,18], and adaptations that could result in improved efficiency [5,9,12,24,25,33]. Furthermore, it is suggested that there are potential performance benefits of improved efficiency as Jeukendrup and& Martin [21] calculated that increasing gross efficiency by 1%, for a 70 kg cyclist who can maintain a power output of 400 W for 1 h, would result in a 48s improvement for a timetrial over 40 km.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the laboratory practice of recording these measures [19,23,28,32], the impact of training status and interventions [1,7,15,16,17,26], gender [3,18], and adaptations that could result in improved efficiency [5,9,12,24,25,33]. Furthermore, it is suggested that there are potential performance benefits of improved efficiency as Jeukendrup and& Martin [21] calculated that increasing gross efficiency by 1%, for a 70 kg cyclist who can maintain a power output of 400 W for 1 h, would result in a 48s improvement for a timetrial over 40 km.…”
Section: Introductionmentioning
confidence: 99%
“…23.9% for older and young, respectively). Other researchers (Bell & Ferguson, 2009;Hopker et al, 2013;Peiffer, Abbiss, Sultana, Bernard, & Brisswalter, 2016;Sacchetti et al, 2010), who did not control either power output or cadence, reported similar trends indicating older adults had 4-18% poorer efficiency compared to young adults during submaximal cycling. Our age-related differences in metabolic cost of cycling are lower compared to those reported for walking.…”
Section: Discussionmentioning
confidence: 83%
“…These chosen cadences also fell within the range of cadences (i.e. 40-120 rpm) used in previous research investigating mechanical and physiological efficiency in older cyclists (Bell & Ferguson, 2009;Hopker et al, 2013;Sacchetti et al, 2010). Pilot testing of these power output-cadence conditions revealed these conditions were challenging and yet achievable for recreationally active older men.…”
Section: Data Collectionmentioning
confidence: 97%
“…The differences between genders seem to fundamentally occur due to the body size and composition. Although the composition of the muscle fibers is similar in both genders (7,28) , the volume of each fiber seems to be greater in men.…”
Section: Discussionmentioning
confidence: 85%
“…Bell and Ferguson (28) showed in young women, high correlations of the type I myosin heavy chain in 60 and 75 revolutions per minute in cycle ergometer (r = 0.80 and r = 0.84, respectively), when confronted with the mechanical efficiency. These cadences were similar to the ones applied in the present investigation.…”
Section: Discussionmentioning
confidence: 96%